PERAN GURU MI DALAM MENINGKATKAN MINAT BELAJAR SISWA TERHADAP MATA PELAJARAN SENI BUDAYA DI MADRASAH IBTIDAIYAH AL-ISLAMIYAH KARANGANYAR - Agustin Septia Paramita; Muhammad Musfi El Iq Bali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the role of Madrasah Ibtidaiyah (MI) teachers in increasing students' learning interest in cultural arts subjects at MI Al-Islamiyah Karanganyar, Paiton District, Probolinggo Regency. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that teachers play the role of facilitators, motivators, and supervisors in creating an active and fun atmosphere of art learning. The strategies implemented include a variety of learning methods, the use of local media, and the provision of appreciation for students' work. The students' response to cultural arts learning was very positive, characterized by enthusiasm, active involvement, and a sense of pleasure in participating in activities. The support from the school is quite good, but parental involvement still needs to be improved. The obstacles faced by teachers include limited facilities and infrastructure, lack of special training, and limited lesson time. This study concludes that the active and creative role of teachers is very decisive in building students' interest in learning arts and culture, although systemic support from schools and parents is still needed so that art learning can run optimally.